Relationships between performance test and match-related physical performance parameters - Altmann, S.; Kuberczyk, M.; Ringhof, S.; Neumann, R.; Woll, A. (German Journal of Exercise and Sport Research, 2018)
Background: The purpose of this study was to analyze the relationship between performance test parameters and match-related physical performance in professional soccer players. Methods: To determine physical capacity, 28 male soccer players underwent several performance tests at the start of the seasons 2013/2014, 2014/2015, and 2015/2016. The following parameters were assessed: maximum running velocity (vmax), fixed (v4mmol/l) and individual anaerobic threshold (vIAS) during an incremental treadmill test; 30-m sprint time in a linear sprint test (LS30m); in a repeated-sprint test, the 30-m sprint time (RST30m) and performance decrement (RSTdecr); and countermovement jump height (CMJ). Match physical performance was quantified during the first ten official matches of each season using a computerized, camera-based tracking system. The following measures of match physical performance were considered: top running speed (TS), mean running speed (vØ), total distance covered (TD), number of sprints (SP), number of high-intensity running (HIR), and aerial duels won (AD+). Pearson correlation coefficients were used for statistical analysis. Results: Moderate to very large correlations were found between the majority of performance test parameters and match performance variables, with a variability of correlations across the three seasons. Large relationships across all three seasons were only observed between vmax and TD, vmax and vØ, LS30m and TS as well as RST30m and TS. Conclusion: This study demonstrates the relationship between several performance test parameters and match-related physical performance in professional soccer players, thereby supporting the test parameters` criterion validity. vmax, LS30m, and RST30m seem to be the most consistent parameters. Hintergrund: Ziel der vorliegenden Studie war es, den Zusammenhang zwischen Leistungstestparametern und der spielbezogenen körperlichen Leistung bei Berufsfußballern zu analysieren. Methoden: Zur Bestimmung der körperlichen Leistungsfähigkeit absolvierten 28 männliche Fußballspieler verschiedene Leistungstests zu Beginn der Spielzeiten 2013/2014, 2014/2015 und 2015/2016. Folgende Parameter wurden ermittelt: maximale Laufgeschwindigkeit (vmax), fixe (v4mmol/l) und individuelle anaerobe Schwelle (vIAS) in einem Laufbandstufentest; 30-m-Sprint-Zeit in einem linearen Sprinttest (LS30m); 30-m-Sprint-Zeit (RST30m) und Leistungsrückgang (RSTdecr) in einem Sprintwiederholungstest; Sprunghöhe in einem Countermovement-Jump (CMJ). Die spielbezogene physische Spielleistung wurde während der ersten zehn offiziellen Spiele jeder Spielzeit mithilfe eines computergestützten, kamerabasierten Tracking-Systems quantifiziert. Die folgenden Maße der spielbezogenen physischen Spielleistung wurden berücksichtigt: Spitzenlaufgeschwindigkeit (TS); mittlere Laufgeschwindigkeit (vØ); zurückgelegte Gesamtstrecke (TD); Anzahl der Sprints (SP); Anzahl der hochintensiven Läufe (HIR); gewonnene Luftzweikämpfe (AD+). Für die statistische Analyse wurden Pearson-Korrelationskoeffizienten herangezogen. Ergebnisse: Moderate bis sehr starke Korrelationen wurden zwischen der Mehrzahl der leistungsdiagnostischen Parameter und der physischen Spielleistung gefunden, wobei eine Variabilität der Korrelationen über die drei Spielzeiten hinweg erkennbar war. Starke Zusammenhänge über alle drei Spielzeiten zeigten sich nur zwischen vmax und TD, vmax und vØ, LS30m und TS sowie RST30m und TS. Schlussfolgerung: Die vorliegende Studie zeigt den Zusammenhang zwischen verschiedenen leistungsdiagnostischen Parametern und der physischen Spielleistung bei Profifußballern. Damit stützt sie die Kriteriumsvalidität der leistungsdiagnostischen Parameter. vmax, LS30m und RST30m scheinen die beständigsten Parameter zu sein.